Late Presentation of Breast Cancer in Lower- and Middle-Income Countries - Clegg-Lamptey, J.N.A.; Vanderpuye, V.; Dedey, F. (Springer Nature, 2019)
Purpose of Review Breast cancer incidence and mortality in low- and medium-income countries has increased and is predicted to rise. Late presentation, associated with poor prognosis, is unfortunately common to most of these countries. This review discusses recent studies and offers recommendations to address pertinent issues raised. Recent Findings Late presentation continues to prevail in many LMICs, worse in sub-Saharan Africa. Socioeconomic and demographic factors play a significant role. The fear of mastectomy is a prominent cause of reluctance to seek treatment. Increasing awareness, clinical breast examination and opportunistic mammographic screening have a role to play in addressing the issue. The provision of health infrastructure and creating access may overcome some of the other factors that sometimes seem unsurmountable.
Research Article
Keywords: Late presentation; Breast cancer; Low- and middle-income countries; Mastectomy